Pengaruh Tingkat Bunga Terhadap Biaya - I Nyoman Widana (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2011)
This article discusses the impact of interest rates on expense rates. An insuranceexpense is the difference calculated between Gross Premium and Net Premium. The calculationsindicate that the expense reduces when the interest rate increases.